2000
DOI: 10.1086/501758
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Factors of Ventilator-Associated Pneumonia in a Riyadh Hospital

Abstract: We report the incidence of, and risk factors for, ventilator-associated pneumonia (VAP) at the King Fahad National Guard Hospital. Of the 202 patients studied, 41 (25.2%) had VAP. The incidence density was 16.8/1,000 person-days of ventilation. Variables significantly associated with VAP were serious injury from motor-vehicle accident, enteral feeding, and length of ventilation. The avoidance of unnecessary enteral nutrition could help to reduce VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 8 publications
2
22
2
1
Order By: Relevance
“…Also in our study, the most common pathogens were Gram-negative bacteria. Furthermore, prior antibiotic therapy and COPD, leading to colonization with Gram-negative aerobic pathogens, were reported to be risk factors for the development of NP [11,28,30,34]. In our patient population, univariate analysis suggested that previous antibiotic treatment and COPD increased the risk of pneumonia, but interestingly they were not independent risk factors in multivariate analysis.…”
Section: Discussionmentioning
confidence: 62%
“…Also in our study, the most common pathogens were Gram-negative bacteria. Furthermore, prior antibiotic therapy and COPD, leading to colonization with Gram-negative aerobic pathogens, were reported to be risk factors for the development of NP [11,28,30,34]. In our patient population, univariate analysis suggested that previous antibiotic treatment and COPD increased the risk of pneumonia, but interestingly they were not independent risk factors in multivariate analysis.…”
Section: Discussionmentioning
confidence: 62%
“…There are several risk factors that have been found related to occurrence of VAP, including reintubation, enteral feeding, parenteral nutrition, transfusion, bronchopulmonary dysplasia, and length of stay in the NICU. 8,11,[26][27][28][29] However, these various results may be due to different study populations, study designs, inclusion or exclusion criteria of VAP, and analytic methods.…”
Section: Discussionmentioning
confidence: 99%
“…o papel da idade e do escore APACHE ii como fatores de risco para infecção ainda está em discussão. Enquanto alguns estudos demonstraram que estas variáveis são fatores de risco significativos 24 , outros autores não encontraram tal associação 25,26 . neste estudo a idade e o APACHE ii não foram fatores de risco significativos para o desenvolvimento de PAV, embora outro escore de gravidade, tiSS, tenha sido associado com aumento do risco.…”
Section: Discussionunclassified